2014
DOI: 10.1007/s12028-014-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-convulsive Status Epilepticus and Non-convulsive Seizures in Neurological ICU Patients

Abstract: Specific clinical features along with history and imaging findings may be used to identify patients at high risk of NCSE/NCS in the neurological ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 49 publications
7
69
2
Order By: Relevance
“…This is in keeping with hospital LOS of 12 days previously reported among the NCS/NCSE population [34]. The longer LOS in the wean group may be due to several reasons.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in keeping with hospital LOS of 12 days previously reported among the NCS/NCSE population [34]. The longer LOS in the wean group may be due to several reasons.…”
Section: Discussionsupporting
confidence: 91%
“…While some studies show that within the NCS/NCSE group, subjects with generalized ictal discharges had a worse prognosis compared to subjects with unilateral ictal discharges [34], others did not find any prognostic correlation with abnormal or epileptiform EEG [31]. In the context of AED withdrawal, a number of studies have identified factors associated with increased risk of relapse including multiple seizure types, focal epileptiform abnormalities on EEG, and worsening EEG patterns after AED discontinuation [29,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study of people with altered mental status, NCSE or nonconvulsive seizures were documented in 21% of patients; 25% of these patients had prior seizures that were clinically apparent. One‐half of these patients had subtle findings such as muscle twitching or eye deviation . NCSE may occur before or after convulsive seizures are apparent; therefore, NCSE should be considered in any patient with a prolonged postictal state, or in an immobile patient experiencing a prolonged period of impaired consciousness following the treatment of CSE, especially after the withdrawal of anesthetics and sedatives used to control SE .…”
Section: Diagnosis Of Status Epilepticusmentioning
confidence: 99%
“…In addition, the frontal lesion was more strongly associated with NCSE compared with CSE. Other previous studies reported that NCSE was most strongly associated with the temporal region followed by the frontal region [20,21]. After ischemic stroke, NCSE was more frequently observed in the anterior versus the posterior circulation infarct [14].…”
Section: Discussionmentioning
confidence: 81%